Turn-taking model for Filipinos’ high-context communication style from no-answered and non-answered questions in faculty meetings - Munalim, Leonardo O.; Genuino, Cecilia F.; Tuttle, Betty E. (Penerbit Universiti Kebangsaan Malaysia, 2022)
Interrogativity is a linguistic property in all world languages. It is inherently related to the ‘question-answer’ tandem of turn-taking. One notable feature of turn-taking is the adjacency pairs, where the question-and-answer sequences are part of. The canonical turn-taking model by Sacks et al. (1974) highlights the obligation to answer the questions. In this paper, however, we report the many cases of no-answered and non-answered questions in faculty meetings using the analytical framework of Conversation Analysis. We show that the Filipinos’ high-context communication style has impinged on the occurrences of these types of answers. We then illustrate a turn-taking model for this type of communication, wherein a straightforward answer is no longer obligatory, but becomes optional within the frame of high-context communication style of the Filipino context. The questioning party can just “let it go” and accept the indirect response as a legitimate and true answer to the question. Towards the end, we argue that the results may convey that the faculty meeting, which is considered as an institutional talk, has resembled ordinary mundane conversations, where questions are oftentimes taken for granted.